2013
DOI: 10.1039/c3tc00639e
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative X-ray absorption and emission spectroscopies: electronic structure elucidation of Cu2S and CuS

Abstract: The electronic structures of Cu2S and CuS have been under intense scrutiny, with the aim of understanding the relationship between their electronic structures and commercially important physical properties. Here, X-ray absorption and emission spectroscopic data have been analyzed using a quantitative, molecular orbital (MO) based approach to understand the electronic structure of these two complex systems. Cu2S is shown to have a significant amount of Cu2+ sites and therefore Cu0 centers. The presence of low-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
113
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(123 citation statements)
references
References 41 publications
10
113
0
Order By: Relevance
“…In addition, the chemometrics of the Cu/S ratio of 1.01 suggests that the sample should be pure CuS. The valance of Cu element in CuS is uncertain until now, Liang et al reported a (Cu 1+ ) 3 [20] and Kumar suggested both Cu 1+ and Cu 2+ exist in covellite CuS [21]. The XPS pattern of Cu is shown in Figure 1(c).…”
Section: Resultsmentioning
confidence: 91%
“…In addition, the chemometrics of the Cu/S ratio of 1.01 suggests that the sample should be pure CuS. The valance of Cu element in CuS is uncertain until now, Liang et al reported a (Cu 1+ ) 3 [20] and Kumar suggested both Cu 1+ and Cu 2+ exist in covellite CuS [21]. The XPS pattern of Cu is shown in Figure 1(c).…”
Section: Resultsmentioning
confidence: 91%
“…and S 2-ions surrounded by CuS 4 tetrahedron of Cu ? and S 2 2-ions (Kumar et al 2013). Recently, CuS nanoparticles have been used as photocatalysts for the degradation of organic dyes such as MB, methyl red, methyl orange, Rhodamine B, and 2,4-dichlorophenol.…”
Section: Introductionmentioning
confidence: 97%
“…The crystal phase called covellite (CuS) supplements the copper sulfide family with unique physical properties like high holes concentration (up to 10 22 cm -3 [19]) based on the specific crystal structure. Additionally the high degree of hole delocalization is inherent to the covellite phase [24], as well as distinct anisotropic metallic conductivity [25]. Thus, this semiconductor shows a highly pronounced localized surface plasmon resonant (LSPR) absorption peak appearing in the NIR [26] (in the second biological spectral window, 1000-1350 nm [27,28]) in comparison to gold, silver and copper, which are located in the visible range.…”
Section: Introductionmentioning
confidence: 99%